Green synthesis of silver and gold nanoparticles using Crataegus oxyacantha extract and their urease inhibitory activities. (17th September 2020) - Ali, Shujat; Bacha, Misal; Shah, Muhammad Raza; Shah, Wahid; Kubra, Khadijatul; Khan, Ajmal; Ahmad, Manzoor; Latif, Abdul; Ali, Mumtaz
Abstract: This study reports the green synthesis and urease inhibitory activities of Ag and Au nanoparticles (NPs) using Crataegus oxyacantha extract. The synthesized NPs were characterized by UV–visible, FT‐IR spectroscopy, atomic force microscopy, and scanning electron microscopy. The obtained NPs were spherical in shape, and their size was around 85 nm. A strong correlation between the phytochemicals present in the extract and their capability for the synthesis of NPs was observed. Furthermore, the shape, size, stability, and bioactivity of the NPs were strongly influenced by the stabilizing phytochemicals. The experimental analysis suggested that these NPs have substantial stability in a diverse range of physiological conditions such as pH, salinity, and temperature. The NPs exhibited potent urease enzyme inhibitory activities with percent inhibition of 99.25 and IC50 value of 1.38 ± 0.3, comparable to the standard (thiourea percent inhibition, that is, 98.2% and IC50 value 5.3 ± 0.04). These results suggested that the proposed NPs could be used in the homeopathic and pharmaceutical industries for biomedical applications. Abstract : Extract fractions from Crataegus oxyacantha were used as reducing and stabilizing agents for Ag and Au NPs. The as‐synthesized NPs exhibited good urease inhibitory activities. The strategy can be applied for physiologically stable, cheap and non‐toxic Ag and Au NPs for biomedical applications.